The Efficacy of Trimethoprim-sulfamethoxazole Compared to Ciprofloxacin in The Treatment of Spontaneous Bacterial Peritonitis in Cirrhotic Patients with Ascites - Syadra Bardiman Rasyad; Ahmar Kurniadi; Fuad Bakry Fauzi (The Indonesian Society for Digestive Endoscopy, 2002)
Background: The incidence of spontaneous bacterial peritonitis (SBP) is 7 to 23%, and the associated mortality rate is 25 to 40% (Rimola 1992). The aim of this study was to evaluate the efficacy of trimethoprim-sulfamethoxazole compared to ciprofloxacin in the treatment of SBP in cirrhotic patients with ascites. Materials and Method: This prospective randomized double blind study included 43 cirrhotic patients with ascites (25 males, 18 females, ages 23-75 years, one female patient died prior to laboratory evaluation) enrolled between May 1999 and June 2000, at the Department of Internal Medicine of Mohammad Hoesin General Hospital /the Medical Faculty of Sriwijaya University of Palembang, South Sumatera. Twenty-three patients (53.4%) with SBP were eligible for the study, all were randomized. Patients were divided into 2 groups (13 in group I, and 10 in group II), those receiving trimethoprim- sulfamethoxazole 960 mg once daily for 10 days and those receiving ciprofloxacin 1000 mg once daily for 10 days. Statistically, there was no significant difference in the characteristics of the 2 groups. Results: The incidence of SBP in our study was 53.4% (23 patients out of 43 cirrhotic patients with ascites). The Results of the study demonstrate that trimethoprim-sulfamethoxazole and ciprofloxacin are both effective (91.6% and 90%) in the treatment of SBP. There was a significant decrease in ascitic fluid PMN count after 10 days treatment with both of the drugs (p=0.001 and p=0.000). There was no statistically significant difference (t-test) between the two groups in decreasing the ascitic fluid PMN count after the treatment (p=0.664). Conclusion: Trimethoprim-sulfamethoxazole and ciprofloxacin has similar efficacy in the treatment of spontaneous bacterial peritonitis in cirrhotic patients with ascites. Keyword: Trimethoprim-sulfamethoxazole, ciprofloxacin, spontaneous bacterial peritonitis.